Short-period g-mode pulsations in low-mass white dwarfs triggered by H-shell burning - Corsico, Alejandro Hugo (2014)
The detection of pulsations in white dwarfs with low mass offers the possibility of probing their internal structures through asteroseismology and placing constraints on the binary evolutionary processes involved in their formation. In this Letter, we assess the impact of stable H burning on the pulsational stability properties of low-mass He-core white dwarf models resulting from binary star evolutionary calculations. We found that besides a dense spectrum of unstable radial modes and nonradial g and p modes driven by the κ mechanism due to the partial ionization of H in the stellar envelope, some unstable g modes with short pulsation periods are also powered by H burning via the ɛ mechanism of mode driving. This is the first time that ɛ destabilized modes are found in models representative of cool white dwarf stars. The short periods recently detected in the pulsating low-mass white dwarf SDSS J111215.82+111745.0 could constitute the first evidence of the existence of stable H burning in these stars, in particular in the so-called extremely low-mass white dwarfs.